Resveratrol, pterostilbene, and baicalein: plant-derived anti-biofilm agents - Kolouchová, Irena; Maťátková, Olga; Paldrychová, Martina; Kodeš, Zdeněk; Kvasničková, Eva; Sigler, Karel; Čejková, Alena; Šmidrkal, Jan; Demnerová, Kateřina; Masák, Jan (Folia microbiologica, 2018)
Microbial adhesion to surfaces and the subsequent biofilm formation may result in contamination in food industry and in healthcare-associated infections and may significantly affect postoperative care. Some plants produce substances with antioxidant and antimicrobial properties that are able to inhibit the growth of food-borne pathogens. The aim of our study was to evaluate antimicrobial and anti-biofilm effect of baicalein, resveratrol, and pterostilbene on Candida albicans, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Escherichia coli. We determined the minimum inhibitory concentrations (MIC), the minimum adhesion inhibitory concentration (MAIC), and the minimum biofilm eradication concentration (MBEC) by crystal violet and XTT determination. Resveratrol and pterostilbene have been shown to inhibit the formation of biofilms as well as to disrupt preformed biofilms. Our results suggest that resveratrol and pterostilbene appear potentially very useful to control and inhibit biofilm contaminations by Candida albicans, Staphylococcus epidermidis, and Escherichia coli in the food industry.
Keywords: Staphylococcus epidermidis; Candida albicans; Anti-Infective Agents; biofilmy; Microbial Sensitivity Tests; flavanony; rostlinné extrakty; Biofilms; mikrobiální testy citlivosti; stilbeny; Escherichia coli; Pseudomonas aeruginosa; Resveratrol; Flavanones; Stilbenes; antiinfekční látky; Plant Extracts; resveratrol